The County Agent's Newsletter - Is It A Sleeping Giant? - Robert E. Thomas (Journal of Applied Communications, 1987)
For years now, county agents have been encouraged to produce newsletters as one effective way to reach their clientele. If you haven't lately, you might want to check in your state to see just how good of a job they have done.